MANAJEMEN KEPEMIMPINAN KIAI DALAM UPAYA PENINGKATAN MUTU PESANTREN BERBASIS ISLAM MODERAT - Atik Silvia; Ali Nurhadi (Pascasarjana PAI Multikultural Universitas Yudharta Pasuruan, 2023)
Moderate Islam maust be the main feature of everi Islamic boarding school. History proves that the showing of moderate teaching in religion is in Islamic boarding School. Islamic boarding schools are Islamic educational institutions that the kiai as the central figure. The quality of the pesantren is determined by the kiai as the leader of the Islamic boarding school who drives all activities in it. Islamic boarding schools will give birth to qualified santri graduates if the management of the kiai's leadership is carried out properly. Through a literature study using a qualitative approach, this research focuses on the concept of kiai leadership, kiai management in Islamic boarding schools, and analysis of kiai leadership management in efforts to improve the quality of Islamic boarding schools based on moderate Islam. The results of the study found that kiai leadership is the ability of a kiai to organize and manage the pesantren educational institution he leads and has the highest role in it. The function of kiai management in Islamic boarding schools as an effort to improve the quality of Islamic boarding schools includes planning carried out with the leaders of educational units and administrators of Islamic boarding schools, organizing by delegating tasks according to their expertise, actuating with the assistance of pesantren stakeholders, and controlling in an effort to improve if there are problems in the program that has been implemented according to the previous plan.Keywords: Management; Kiai leadership; Islamic boarding school quality, Moderate Islam